(untitled) (Eurasian Research Bulletin, 2025)
This article examines the significance and effectiveness of pedagogical mechanisms in developing digital competencies of future engineers in engineering education. It analyzes how project-based learning, simulation software, coding exercises, interactive teaching methods, and online platforms contribute to the development of technical, creative, communicative, and collaborative skills among students. The study also addresses challenges in fostering digital competencies, including limitations in technological infrastructure, faculty digital proficiency, and variations in student motivation